2010
DOI: 10.1097/iae.0b013e3181b32eef
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Iris Claw Intraocular Lens Implantation for the Correction of Aphakia After Pars Plana Vitrectomy

Abstract: Secondary iris claw intraocular lens implantation is clinically safe and effective to correct aphakia in vitrectomized eyes without capsular support. Larger studies with longer follow-up are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…Complication rates were comparable in the present study to similar previous studies (9,10) . Previous studies have used iris claw lenses for iris fixation to correct aphakia in vitrectomized eyes (25,26) . While the lack of suture usage was an advantage in these studies, the requirement of a large incision and anterior chamber implantation were disadvantages (25,26) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complication rates were comparable in the present study to similar previous studies (9,10) . Previous studies have used iris claw lenses for iris fixation to correct aphakia in vitrectomized eyes (25,26) . While the lack of suture usage was an advantage in these studies, the requirement of a large incision and anterior chamber implantation were disadvantages (25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used iris claw lenses for iris fixation to correct aphakia in vitrectomized eyes (25,26) . While the lack of suture usage was an advantage in these studies, the requirement of a large incision and anterior chamber implantation were disadvantages (25,26) . Two major methods of suture-free intrascleral IOL implantation have been reported in previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acar et al found a significant increase in mean CMT in the third month in 12 ICL implantation cases. 5 Cystoid macular edema was detected by RTVue-100 ® Fourier-Domain OCT in the third month postoperatively in one patient who underwent retropupillary ICL implantation. CME was not detected in any of the patients who underwent SFIOL implantation.…”
Section: 11mentioning
confidence: 99%
“…4 ICL implantation anterior to the iris or placed retropupillary, with its relative ease of implantation compared to other methods and its advantage of a shorter operation time, is preferred in vitrectomy and keratoplasty operations. [5][6][7] The learning period of the surgeon for the enclavation technique is lengthy, requiring skill and dexterity. The number of intraoperative and postoperative complications is relatively lower than other techniques.…”
mentioning
confidence: 99%